2014
DOI: 10.1186/1746-4811-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of polysaccharides in the tomato cell wall with Raman microspectroscopy

Abstract: BackgroundThe primary cell wall of fruits and vegetables is a structure mainly composed of polysaccharides (pectins, hemicelluloses, cellulose). Polysaccharides are assembled into a network and linked together. It is thought that the percentage of components and of plant cell wall has an important influence on mechanical properties of fruits and vegetables.ResultsIn this study the Raman microspectroscopy technique was introduced to the visualization of the distribution of polysaccharides in cell wall of fruit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…Regarding that plant cells are on average some of the largest eukaryotic cells, in general both techniques have sufficient spatial resolution for the analysis of plant cells and tissues. FTIR and Raman have been applied extensively on various plant structures, such as cell walls, seeds, and leaves, for research on plant physiology, developmental biology, genetics and ecology (Gorzsas et al 2011;Barron et al 2005;Dokken et al 2005;Chen et al 2013;Yu 2011;Gierlinger and Schwanninger 2006;Chylińska et al 2014;Agarwal 2006;Fackler and Thygesen 2013;Gierlinger et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Regarding that plant cells are on average some of the largest eukaryotic cells, in general both techniques have sufficient spatial resolution for the analysis of plant cells and tissues. FTIR and Raman have been applied extensively on various plant structures, such as cell walls, seeds, and leaves, for research on plant physiology, developmental biology, genetics and ecology (Gorzsas et al 2011;Barron et al 2005;Dokken et al 2005;Chen et al 2013;Yu 2011;Gierlinger and Schwanninger 2006;Chylińska et al 2014;Agarwal 2006;Fackler and Thygesen 2013;Gierlinger et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Differences between skin surfaces are not obvious at first sight (data not shown). A tentative assignment is shown in Table 3 [28,30,31,[49][50][51]. Fig.…”
Section: 3raman Datamentioning
confidence: 98%
“…Taking into account the fact that there are significant differences in these bands among the different grape skin surfaces, they could be mainly ascribed to the aliphatic material presents in the plant cuticle. The band at 1123 cm -1 is due to symmetric stretching of glycosidic C-O-C bonds in cellulose and other polysaccharides [31]. The band at 1342 cm -1 is due to HCC, HCO, HOC bending in cellulose [50] and finally, the band at 1606 cm -1 is due to stretching of aromatic rings of the remaining phenolic compounds [51].…”
Section: 3raman Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Chylinska et al have demonstrated that it is possible to distinguish cellulose and pectins in the cell wall of tomato tissue from minimally prepared samples by employing MCR-ALS analysis. 47 Moreover, their distributions were also visualized with high specificity, which is otherwise not possible using single band imaging. Recently, Liu et al utilized hyperspectral stimulated Raman scattering microscopy coupled with MCR-ALS to reveal spatial distribution of functional groups of lignin in plant cell walls.…”
Section: ·1 Cell Wall Polysaccharide Imagingmentioning
confidence: 99%